Persistence of Herpetofaunal Assemblages in Anthropogenic Landscapes: Insights from Rural Bangka Island, Indonesia - Randi Syafutra; Nurzaidah Putri Dalimunthe; Sujadi Priyansah; Hendi Hendra Bayu; Helvina Handayani; Abdul Kamal; Nur Azizah Nawang Wulan; Reani Febriyani; Rydhollah Arrahmaan (BIO PALEMBANICA, 2025)
Anthropogenic land-use change is a primary driver of global biodiversity loss, yet rural agricultural matrices often retain significant ecological function. This study assesses the composition, diversity, and microhabitat associations of herpetofauna in two human-modified landscapes (Air Duren and Cengkong Abang) in Bangka Regency, Indonesia. Fieldwork was conducted over three consecutive weeks in July 2022 using a time-constrained Visual Encounter Survey (VES) method (19:00–21:00). We recorded 13 individuals representing 7 species and 6 families. The assemblage was dominated by generalist amphibians (Fejervarya cancrivora, Duttaphrynus melanostictus) and synanthropic reptiles (Eutropis multifasciata, Gekko smithii). Notably, Cengkong Abang hosted forest-associated arboreal species, including Tropidolaemus wagleri, Boiga dendrophila, and Ahaetulla prasina, correlating with its higher structural vegetation complexity. Diversity analysis revealed a higher Shannon-Wiener index in Cengkong Abang (H' = 1.75) compared to Air Duren (H' = 1.33). The presence of arboreal and semi-aquatic guilds indicates that rural matrices can function as permeable habitats and secondary refugia. Conservation strategies in Bangka should prioritize the retention of vegetation complexity and stratified canopies within village landscapes to sustain herpetofaunal biodiversity.